2010
DOI: 10.1002/pd.2603
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in participation in prenatal screening for Down syndrome: A register‐based study

Abstract: Compared to Dutch women, those from Turkish, North-African, Aruban/Antillean and other non-Western ethnic origin were less likely to participate in screening. It was unexpected that women from Surinamese origin equally participated. It should be further investigated to what extent participation and non-participation in these various ethnic groups was based on informed decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 21 publications
3
35
1
Order By: Relevance
“…Contrary to our findings, Fransen et al found a lower CT uptake among non-western women (around 12%) [13]. The differences in results could probably be find in a different study design.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings, Fransen et al found a lower CT uptake among non-western women (around 12%) [13]. The differences in results could probably be find in a different study design.…”
Section: Discussioncontrasting
confidence: 99%
“…Fransen et al. used data of one specific Medical Diagnostic Centre in a high density immigrant area, and in our national study, we collected data by purposive sampling; furthermore, the percentage non-Dutch women in our sample was lower compared to the non-Dutch pregnant population and the other study (respectively 17% and 34%) [13]. Also surprisingly, in our study non-western women with a non-Dutch background with limited proficiency in Dutch were more likely to have a CT. An explanation of the higher uptake could be that the women did not have an adequate understanding of the CT [42].…”
Section: Discussionmentioning
confidence: 89%
“…It is likely that higher education implicates a higher ability to gain, interpret and use information on different health offers, health promotion or risk factors. Ethnicity in relation to uptake of prenatal diagnosis has been investigated in several previous studies [1618]. A register-based study in the Netherlands shows that women with a North-African ethnic origin have the lowest participation rate in prenatal screening for Down’s syndrome, only 8% participation rate compared to the higher rate for women with a Dutch (28%) or other Western origin (33%) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Ethnicity in relation to uptake of prenatal diagnosis has been investigated in several previous studies [1618]. A register-based study in the Netherlands shows that women with a North-African ethnic origin have the lowest participation rate in prenatal screening for Down’s syndrome, only 8% participation rate compared to the higher rate for women with a Dutch (28%) or other Western origin (33%) [16]. Also, an Australian study demonstrates that ethnicity is strongly associated with the uptake of prenatal diagnosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Different roles are presented in this model; medical technical expert, advisor and teacher, and counselor in case of exploring values and supporting decision making. The MIMES model identified a number of factors that are relevant in test uptake decisions, including not only well-known factors such as age, parity, family life and personal experience, but also ‘identity markers’ such as ethnicity and religion [10-14]. It is acknowledged that the difficult questions that confront clients in decision-making may be influenced by their religious convictions [15-18].…”
Section: Introductionmentioning
confidence: 99%